Peri-urban forests: an exploratory study of users' recreational activities: The case of the El Meridj-Est recreational forest in Constantine, Algeria - Bouttaba, Chourouk; Nouibat, Brahim; Benmechiche, Meriem (Journal of Degraded and Mining Lands Management, 2024)
Peri-urban forests are wooded areas under the influence of urbanization and are becoming increasingly attractive as recreational areas for urban populations. This study focused specifically on the El Meridj-Est recreational forest, located in Constantine, the capital of eastern Algeria. This study selected this forest as the main case study because of its distinction as the region's most frequented woodland site. This research aimed to understand the practices of 350 users of this forest and to identify the determining factors behind the high affluence at El Meridj. This study also examined their individual and family perceptions, expectations, and concerns, adopting a methodological approach combining detailed qualitative and quantitative social survey techniques. This study fills a research gap in the field of peri-urban green space management with regard to social interactions and recreational activities in these spaces. It also highlights the importance of taking local specificities into account when studying recreational spaces. These results, potentially generalizable to other similar geographical and cultural contexts, offer practical perspectives for the management and conservation of peri-urban forests while minimizing the negative impacts of anthropogenic pressures leading to the degradation of these natural environments.